Studi Kinerja Ruas Jalan Di Sekitar Masjid Terapung BJ. Habibie Kota Parepare - Yusran, Yusran; T, Muh. Nashir; Kasmaida (Jurnal Karajata Engineering, 2024)
Construction of the BJ Habibie Floating Mosque influences the volume and system of traffic movement, the existence of high efficiency has an impact on increased traffic flow and demands the provision of a road network. The aim of this research is to identify the performance of roads and intersections and also to determine the impact on traffic due to the construction of the BJ. Habibie Floating Mosque by using the MKJI 1997 analysis. The results showed that the heaviest traffic flow on the Mattirotasi road section occurred on Saturday at 16.00 until 17.00 WITA with a traffic volume of 220.1 pcu/hour, a v/c ratio of 0.11 and Level of Service A with average vehicle speed 28.77 km/hour. Massepe road section occurred on Sunday at 16.00 until 17.00 with a volume of 943.49 pcu/hour, a v/c ratio of 0.30 and Level of Service B with an average speed of 28.06 km/hour.